Privatisation and the Quest for Sustainable Socio-Economic Development in Nigeria - Jiboku, Joseph O.; Jiboku, Peace A. (NIU Journal of Humanities, 2021)
The issue of development is a universal phenomenon as all countries of the world aspire to make progress and to achieve self-sustaining growth by utilising the resources of nature to make life better. Even so, the need to make life better for the present generation without creating problems for the next one led to the adoption of the concept of ‘sustainable development’ in the academic circle. Thus, bringing the discourse of sustainable development to the Nigerian situation, it is worth identifying that the dwindling fortune of the 1980s as a result of the sharp drop in international oil prices led to the adoption of the policy on Privatisation and removal of government subsidies on government companies and parastatals as a strategy to enhance national development. However, with the consciousness of scholars and policy analysts about the orientation of private investors which is first tailored to profit making, the issue of privatisation has aroused several questions. Some observe that the policy on privatisation is antithetical to development. Importantly too, is the concern that private investors may not be concerned with the future welfare of the society. This paper examines privatisation and Nigeria’s quest for sustainable development. It draws explanations from the Social Contract Theory to highlight the reciprocal relationship between the state and society and the functions and obligations of each parties. With this, the paper analyses issues of debates and contestations on privatisation. Bearing in mind Nigeria’s political economic history and current socio-economic challenges confronting the state, the paper advocates the need for caution and human face in the approach to privatisation. Keywords:    Economic Efficiency, Economic Growth, Privatisation, Public Enterprises, State-Owned Enterprises, Development, Sustainable Development.